Diabetic encephalopathy: Pathogenesis, clinical manifestations, therapy approaches - I. Kh. Khairullin; S. T. Zyangirova; Yu. N. Isayeva; O. R. Esin (Klinicist)
The paper considers the epidemiology, morphology, and clinical manifestations of diabetic encephalopathy. It shows the differences of diabetic encephalopathy in types 1 and 2 diabetes mellitus. Pathogenetic treatment options for diabetic encephalopathy are given.